2010
DOI: 10.1590/s1516-89132010000100003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wastewater from a cassava industry on soil chemistry and crop yield of lopsided oats (Avena strigosa Schreb.)

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
(6 reference statements)
0
4
0
2
Order By: Relevance
“…Bertonha et al (2012), for Brachiaria brizantha cv. MG-5, Cabral et al (2010), for black oat, and Barreto et al (2014), for maize, also observed positive effects on the DM production with the utilization of wastewater.…”
Section: Resultsmentioning
confidence: 87%
“…Bertonha et al (2012), for Brachiaria brizantha cv. MG-5, Cabral et al (2010), for black oat, and Barreto et al (2014), for maize, also observed positive effects on the DM production with the utilization of wastewater.…”
Section: Resultsmentioning
confidence: 87%
“…De acordo com Cabral et al (2010) a espécie aveia preta (Avena strigosa) cultivada em campo apresentou acúmulo de matéria seca em resposta à aplicação de doses do efluente de fecularia. Os autores relataram que a utilização de uma dose de manipueira igual a 376 m 3 ha -1 foi a que rendeu maior acúmulo de massa seca (212 g planta -1 ) em virtude principalmente do alto teor de potássio e nitrogênio existente no resíduo utilizado corroborando os resultados obtidos nesta pesquisa; por outro lado, as respostas de matéria seca da parte aérea das plantas obtidas divergem das encontradas por Inoue et al (2011).…”
Section: Resultsunclassified
“…Resposta semelhante obtiveram Cabral et al (2010), quando utilizaram efluente de manipueira para a adubação do solo e cultivaram aveia preta. Além disso, os autores constataram que apenas o teor de potássio aumentou nas camadas do solo enquanto os outros elementos apresentaram redução.…”
Section: Parâmetros Teorunclassified